Quality assurance of four-dimensional computed tomography in a multicentre trial of stereotactic body radiotherapy of centrally located lung tumours - Marie Lambrecht; Jan-Jakob Sonke; Ursula Nestle; Heike Peulen; Damien C. Weber; Marcel Verheij; Coen W. Hurkmans (Physics and Imaging in Radiation Oncology, 2018)
Background and Purpose: Extensive radiation therapy quality assurance (RTQA) programs are needed when advanced radiotherapy treatments are used. As part of the RTQA four dimensional computed tomography (4DCT) imaging performance needs to be assessed. Here we present the RTQA data related to 4DCT procedures used within the context of stereotactic body radiotherapy (SBRT) of centrally located lung tumours. It provides an overview of the 4DCT acquisition methods and achievable accuracy of imaging lung tumour volumes. Materials and Methods: 3DCT and 4DCT images were acquired from a CIRS phantom with spheres of 7.5 and 12.5 mm radius using the institutional scan protocols. Regular asymmetric tumour motion was simulated with varying amplitudes and periods. Target volumes were reconstructed using auto-contouring with scanner specific thresholds. Volume and amplitudes deviations were assessed. Results: Although acquisition parameters were rather homogeneous over the eleven institutions analysed, volume deviations were observed. Average volume deviations for the 12.5 mm sphere were 15% (−4% to 69%) at end of inspiration, 2% (−2% to 9.0%) at end of expiration and 12% (0% to 36%) at mid-ventilation. For the 7.5 mm sphere deviations were 13% (−99% to 65%), 16% (−34% to 66%) and 1% (−13% to 20%), respectively. The amplitude deviation was generally within 2 mm although underestimations up to 6 mm were observed. Conclusions: The expiration phase was the most accurate phase to define the tumour volume and should be preferred for GTV delineation of tumours exhibiting large motion causing motion artefacts when using mid-ventilation or tracking techniques. The large variation found among the institutions indicated that further improvements in 4DCT imaging were possible. Recommendations for 4DCT QA have been formulated. Keywords: Lung cancer, Radiotherapy quality assurance, 4DCT, Tumour motion, Clinical trial, EORTC